2004
DOI: 10.1103/physrevlett.93.226402
|View full text |Cite
|
Sign up to set email alerts
|

Impurities in Noncubic Crystals: Stabilization Mechanisms for Jahn-Teller Ions in Layered Perovskites

Abstract: Mechanisms responsible for the local geometry around Jahn-Teller impurities in K2NiF4 type lattices are shown to be different from those generating the warping in cubic crystals. The present density functional theory calculations reveal that the elastic anisotropy of the host lattice (visible for closed shell impurities) and the electric field created by the rest of lattice ions upon active electrons make it possible to have d(9) ions in an elongated geometry but with a A(1g) ground state. The puzzling differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 14 publications
6
68
0
Order By: Relevance
“…The present results, together with those recently obtained on layered perovskites, 23 stress the importance of ab initio calculations for gaining a better insight into the subtle phenomena related to the JT effect. This is particularly true as regards the barrier energy, B, on which the experimental information is certainly scarce.…”
Section: Final Remarkssupporting
confidence: 79%
See 2 more Smart Citations
“…The present results, together with those recently obtained on layered perovskites, 23 stress the importance of ab initio calculations for gaining a better insight into the subtle phenomena related to the JT effect. This is particularly true as regards the barrier energy, B, on which the experimental information is certainly scarce.…”
Section: Final Remarkssupporting
confidence: 79%
“…10,17,23 This leads to an impurity-ligand distance, R oct , different from R 0 corresponding to the perfect host lattice. In DFT an electronic density displaying cubic symmetry can easily be built for a d 9 impurity through the ͑3z 2 − r 2 ͒ 1.5 ͑x 2 − y 2 ͒ 1.5 configuration.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…32,34 Furthermore, it has been shown that E R (r) plays a key role for understanding the local structure and the associated spectroscopic properties of Cu 2+ -and Cr 3+ -doped layered perovskites such as K 2 AF 4 (A = Mg, Zn). 39 Despite that the mere addition of the internal electric field E R (r) to the CrO 6 9− complex allows one to understand an important number of experimental facts corresponding to the Cr 3+ -based gemstones, there is, however, a fundamental question which needs to be answered. As it has been pointed out, the internal electric field E R (r) will modify the electronic density and covalency inside the CrO 6 9− unit provided V R (r) is not a constant on the whole complex region.…”
mentioning
confidence: 99%
“…A similar case can also be found for Cu 2+ in K 2 MgF 4 crystal. The density functional theory (DFT) calculations [30,44] reveal that the octahedral environment of Cu 2+ in K 2 MgF 4 is tetragonallycompressed. This point is also unlike the corresponding octahedron in the host crystal K 2 MgF 4 , but in agreement with that in the isomorphous pure crystal K 2 CuF 4 [45].…”
Section: Discussionmentioning
confidence: 99%